UAK Data Management Plan - Hamre, Torill; Sandven, Stein; Sagen, Hanne; Storheim, Espen; Monsen, Frode (Zenodo, 2023)
This document is the Data Management Plan for the UAK project. UAK is funded by the INTPART programme 2018-2021 (International partnerships for excellent education, research and innovation) under the Research Council of Norway and the Norwegian Agency for International Cooperation and Quality Enhancement in Higher Education (Diku). The project, which includes partners from Norway, USA and Canada, brings together leading researchers, educators and young scientists working on selected Arctic science topics. The project was also supported by the H2020 project INTAROS – Integrated Arctic Observation System, ( http://intaros.eu , http://intaros.nersc.no ). UAK has organised two research schools onboard Norwegian Coastguard vessel KV Svalbard where students and young scientists have received training in collecting oceanographic, acoustic and sea ice data. Furthermore, the research schools addressed the different steps in the data delivery chain from development of data management plan, collection of data and securing meta data, processing and formatting data, and ingestion into a data system providing a persistent unique identifier (DOI). Prior to the research schools, the students were given training in data management and after the cruises the students were trained in preparing the collected data for publication in a data system that will secure long-term storage and access, along with a DOI for citation. Oceanographic and acoustic data collected during the two research schools have been published in the Norwegian Marine Data Centre (NMDC), in standard formats and with metadata to support discovery, access and reuse. Seismology data collected during the UAK 2020 Research School are stored in the Norwegian National Seismic Network (NNSN). The Research Council of Norway project number 274891.